Temporary mess (making a difference for teens) a guidance activity resource book - Jara, Lito S. (New Day Pub., 1998)
Purpose: "Temporary Mess (Making a difference for teens) is a guidance activity book designed to provide counselors with activities aimed at helping our high school young people understand and know themselves better, and process the experiences they go through during this period."